A generalised 17-state vibronic-coupling Hamiltonian model for ethylene - Jornet-Somoza, Joaquim; Meyer, Hans-Dieter (The journal of chemical physics, 2012)
In a previous work [B. Lasorne, M. A. Robb, H.-D. Meyer, and F. Gatti, “The electronic excited states of ethylene with large-amplitude deformations: A dynamical symmetry group investigation,” Chem. Phys. 377, 30-45 (2010); B. Lasorne, M. A. Robb, H.-D. Meyer, and F. Gatti, Chem. Phys. 382, 132 (2011) (Erratum)], we investigated the electronic structure of ethylene (ethene, C2H4) in terms of 17 dominant configurations selected at the multiconfiguration self-consistent field level of theory. These were shown to be sufficient to recover most of the static electron correlation among the first valence and Rydberg states at all geometries. We also devised a strategy to build a 17-quasidiabatic-state matrix representation of the electronic Hamiltonian for curvilinear coordinates using dynamical symmetry. Here, we present fitted surfaces in the form of a generalised vibronic-coupling Hamiltonian model for two nuclear coordinates, CC bond stretching and torsion. Dynamic electron correlation is included into the electronic structure to improve the energetics of the Rydberg states at the multireference configuration interaction level of theory. The chemical interpretation of the adiabatic states of interest does not change qualitatively, which validates our choice of underlying quasidiabatic states in the model. The absorption spectrum is calculated with quantum dynamics and partially assigned. This first two-dimensional model shows a surprisingly good agreement with the experimental spectrum.